Keterampilan Berpikir Kritis dan Pemecahan Masalah Mahasiswa - Nurul Mulyaningsih; Masduki Asbari; Riska Sri Rahmawati (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to show that students can be sensitive to issues or problems that occur in society so that the character of a "problem solver" is formed. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Gita Wirjawan's YouTube channel entitled "Karlina Supelli: Creation, Taste, and Indonesian Human Will," which she explained. The results of this study explain that students, as agents of change, can bring change to others by applying critical thinking in the problem-solving process. Critical thinking skills are very important for a student. In this case, when students think critically, students will look for as much information as possible to find.